The effectiveness of using a computerized interactive program in improving the five senses concepts for the students of Fourth Primary Grade - Dib, Aosaf; Wahbe, Widad (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The current research aims to know the effectiveness of using the suggested computerized interactive programs of the students achievements through designing a learning computerized Unit in science and know its effectiveness in helping the students of fourth primary grade to gain the basic concepts of the five senses, and to achieve this goal a computerized learning program was designed, educational achievement test and an attitudes questionnaire was designed, and the computerized program was applied on two schools (Ibrahim Hanano & Ammar Hassan) from the first cycle schools in Damascus Al-Muhajreen area, and the number of sample members was (74) pupils. The results showed that the suggested learning computerized Unit is effective in helping the students to improve the basic concepts of the five senses, and there was a difference statistically significant between the mean scores of students in the control group (male/ female) and average grades of students of the experimental group (male/ female) for the benefit of the students of the experimental group, in addition to a difference statistically significant between the average grades of students of the control group and the average grades of students of the experimental group due to the variable of method of education for the benefit of the experimental group, and the results showed that 88.24% of students of the fourth primary grade attitudes were positive toward the learning computerized Unit, with no difference between the students attitudes depending on the sex variable, also the results showed that there is no correlating relationship with significant statistical between the fourth grade pupils marks in the achievement test and their marks in the attitudes questionnaire. And one of the most important research proposals was the necessity to cares about the using of computerized interactive educational programs and the employment of it in the educational process and that's for its impact on the achievement and direction.